Entrepreneurship in Indonesia and Poland Development, Obstacles and Prospects - Anna Bąkiewicz; Tulus T.H. Tambunan (International Journal of Small and Medium Enterprises and Business Sustainability, 2015)
The paper examines the role played by the middle class in the development of European and Asian capitalism. In particular, this comparative study of Indonesia and Poland is to enlarge understanding of the actual and potential importance of the development of entrepreneurship for economic, political and social development. Especially, it aims at drawing some lessons from the experiences of micro, small and medium enterprises (MSMEs), which are generally viewed as the important basis of both entrepreneurship and middle class development in the two countries. This study is based on some premises and observations concerning both the selected economies, the development of entrepreneurship, and the role of MSMEs. This paper presents static and dynamic comparisons of MSMEs development in Indonesia and Poland. Next, the discussion of the determinants of the MSMEs development follows. It covers factors on both global and national levels with the economic policy included. Finally, it tries to identify the consequences of the expansion of the entrepreneurship and the middle class in the two economies for their economic, political and social development. In conclusions the paper suggests some ideas concerning both the role of entrepreneurship in development, the modernization of the MSMEs sector and finally, the institutional support instruments that seem to be economically reasonable